2011
DOI: 10.1002/gps.2782
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to and facilitators for the use of an evidence‐based occupational therapy guideline for older people with dementia and their carers

Abstract: This study generates knowledge for applying innovations in health care settings. Improvement of the OTs' knowledge and self-confidence is needed for using the guideline. We expect that more competent OTs will motivate their physicians and managers to use this successful COTiD intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 22 publications
1
41
0
Order By: Relevance
“…The interventions in the included studies involved intensive training in adhering to study protocol (up to 80 hours). Translational research studies in dementia care have provided approximately 3 days of training to occupational therapists (Gitlin, Jacobs & Earland, 2010;Van't Leven et al 2011). This training needs to be available for both students and clinicians and supported by healthcare organizations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The interventions in the included studies involved intensive training in adhering to study protocol (up to 80 hours). Translational research studies in dementia care have provided approximately 3 days of training to occupational therapists (Gitlin, Jacobs & Earland, 2010;Van't Leven et al 2011). This training needs to be available for both students and clinicians and supported by healthcare organizations.…”
Section: Discussionmentioning
confidence: 99%
“…Further research must be conducted to systematically identify the barriers and enablers to implementation of evidence based occupational therapy in different countries. A study reported by Van't Leven et al (2012) involved training occupational therapists in the Community Occupational Therapy in Dementia (COTiD) intervention ( Van't Leven et al, 2012). Focus groups were conducted to explore barriers to implementation of the program.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 16 studies (regarding a total of 8 interventions) (7,8,21,22,23,49,52,53,54,55,63,70,93,94,122 and 123) discussed changes on how intervention staff delivered the neurological rehabilitation intervention over time. However, this was not described in detail.…”
Section: Recruitmentmentioning
confidence: 99%
“…Van't Leven et al [11] reported that the COTiD was not sufficiently used by occupational therapists who had learned it in a COTiD guideline course at Radboud University. They ascribed this to difficulties in actually implementing the rather complicated treatment, and that therapists had less competence in treating clients at home according to the guidelines.…”
Section: Literature Reviewmentioning
confidence: 99%